1998
DOI: 10.1111/j.1600-0897.1998.tb00069.x
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte Macrophage‐Colony Stimulating Factor Production by Autologous Endometrial Co‐Culture Is Associated with Outcome for In Vitro Fertilization Patients with a History of Multiple Implantation Failures

Abstract: The improved outcome associated with GM-CSF values greater than 130 pg/ml may reflect: 1) a direct positive effect of GM-CSF; 2) an embryotrophic factor upregulated by GM-CSF; or, 3) that GM-CSF functions as a marker for the importance of the glandular component in endometrial co-culture systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 13 publications
1
24
0
4
Order By: Relevance
“…The Cornell group has published several studies demonstrating improvements in blastomere number and decreases in fragmentation rate in patients with a history of poor embryo quality and failed implantation. [33][34][35] All patients in these studies underwent embryo transfer on day 3. The IVI group has investigated the use of AECC with extended culture to the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
“…The Cornell group has published several studies demonstrating improvements in blastomere number and decreases in fragmentation rate in patients with a history of poor embryo quality and failed implantation. [33][34][35] All patients in these studies underwent embryo transfer on day 3. The IVI group has investigated the use of AECC with extended culture to the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
“…Our work has shown that autologous endometrial coculture improves embryo quality through the elaboration of cytokines by the stromal and epithelial cells of the endometrium. It appears that several cytokines (GM-CSF, LIF, and the IL-1 system) are associated with IVF outcome when utilizing autologous endometrial coculture (4)(5)(6). Therefore, the success of our autologous endometrial coculture system is dependent upon an appropriately developed endometrium.…”
Section: Introductionmentioning
confidence: 99%
“…The process of decidualization is characterized by dramatic morphological and biochemical transformation of ESCs into secretory decidual cells that is associated with the production of cytokines, growth factors, and inflammatory mediators essential for blastocyst development and implantation [28,30,31]. For instance, ESCs have been demonstrated to release a number of factors like leukemia inhibitory factor (LIF) [32], granulocytemacrophage colony-stimulating factor (GM-CSF) [33], insulinlike growth factor (IGF) [34], epidermal growth factor (EGF) [35], and IL-6 [36,37] that have been found to exert a direct beneficial effect on embryonic development, growth rates, and implantation potential [3,4,26,38,39].…”
Section: Introductionmentioning
confidence: 99%
“…To date, a wide variety of co-culture systems have been reported to have favorable effects on preimplantation embryo development such as improved growth [3,5,[7][8][9], morphological characteristics [10], and blastocyst development [11]; decreased incidence of fragmentation [3,5,12] and apoptosis [13]; and higher pregnancy [4,10] and delivery rates [14]. Among the broad range of somatic cell lines with welldetermined embryotrophic properties, Vero cells [15][16][17][18], cumulus-granulosa cells [19][20][21][22][23], and endometrial cells from the lining of the uterus [3-5, 11, 12, 24, 25] could be defined as the most popular and commonly used in clinical in vitro fertilization programs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation